ACUTE UPPER RESPIRATORY TRACT INFECTIONS: DIAGNOSTIC CHALLENGES AND THERAPEUTIC APPROACH - Kiełczewski, Krzysztof; Fetner, Barbara; Dłużewska, Magdalena; Zaręba, Agnieszka; Juszkiewicz, Dawid; Adler, Konrad; Stankowska, Patrycja; Gebert, Zuzanna; Ilkiv, Ivanna; Kucharska, Agata (International Journal of Innovative Technologies in Social Science, 2026)
Background. Upper respiratory tract infections (URTIs) remain one of the most prevalent diagnoses in primary care. In medical practice most of them are self-limiting, therefore symptomatic management is the primary approach. Appropriate treatment is beneficial for the patient and for entire healthcare system. Purpose. Aim of this study is to assess advantages and potential risks, when approaching treatment of acute upper respiratory tract infections based on particular etiology, while also highlighting the diagnostic challenges associated with identifying the causative pathogen. Material and Methods. A narrative review was conducted using PubMed and Google Scholar databases. Main focus was put on recent clinical guidelines and research papers. Results. The great diversity of etiological factors causing URTI and very similar clinical presentation means that more specific tests like PCR are required to properly distinguish pathogens. Furthermore, most URTI are of viral etiology, therefore causal treatment is rarely possible. Combining those facts with over-the-counter availability of NSAIDs means that COX-inhibitors became a staple in quick symptomatic relief. Conclusion. Timely intervention in URTI leads to better outcomes and well-being of patients. In cases where etiology-based treatment is available, early intervention may contribute to reducing the infectious period and lowering the risk of hospitalization in high-risk patients. However, the potential increase in antimicrobial resistance should always be considered when making a treatment-related decision involving antibiotics. Objective medical tools, such as the Centor score may aid and quicken the decision process, while ensuring that antibiotics are administered when genuinely indicated.